How to draw Pokemon : gotta catch 'em all - Zalme, Ron. ([Mahwah, NJ] : Troll, 1999)
It takes special skill to advance to the rank of Pokemon Master. It takes practice to learn how to draw your favorite Pokemon. that's where this book comes in. You'll learn step by step how to draw Pikachu, Meowth, Ivysaur and many other Pokemon. Just as a Pokemon Master must show great patience and perseverance, so must a Polemon artist.
Keywords: Pokm̌on (Game); Drawing; Juvenile literature